LISTENING TEAMS: STRATEGI PEMAHAMAN ISI TEKS PADA SISWA SMPN 1 KARANGPLOSO - Sri Handayani (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
This study aims to improve the ability to understand the content of the text using listening strategy teams for seventh grade students of SMP Negeri 1 Karangploso. The design of this study was a two-cycle classroom action research assigning 34 students as research subject. The study revealed that the mastery learning to understand the text content increases in each cycle. Mastery learning was achieved by 17,86% of 34 students in the pre-cycle, 42.86% students in the cycle I, and 85.72% students in the cycle II. In the precycle, insufficient of the mastery learning achieved 82.14%, 57.14% in the cycle I, and 14.28% in the cycle II. This proves that the use of listening teams strategies successfully improved to understand the text coontents.